Comparative antimicrobial activities of extracts of garcinia kola, kola acuminata and kola nitida seeds on isolates of respiratory tract and other infections (2008)
The methanolic extracts of the powdered seeds of Garcinia kola (Guttilerae), Kola acuminata, and Kola nitida (Sterculiaceae) were tested individually for antimicrobial activity using isolates from respiratory tract infections and other sites of infection such as High vagina swab, wounds, urethra and skin. The isolates included Staphylococus aureus (5strains), Z strains each of Escherichia coli, Proteus mirabilis and Streptococcus pneumoniae; I strain each of Streptococcus viridians Entercoccus faecalis, Streptococcus pyogenes, Bacillus subtilis, Haemophillus influenzae, Candida albicans, Asp. Niger, Ap. Eumigatus and Trichophyton specie, and 3 strains each of Pseudomonas aeruginosa and Klebsiella pneumoniae. The antimicrobial susceptibility test of the extracts showed zones of growth inhibition ranging from 9mm to as large as 35mm, depending on the organism being tested. The minimum inhibitory concentration (MIC) was determined by agar-diffusion method and ranged from 0.23mg/ml to 30mg/ml for the three extracts. The crude extracts of Garcinia Kola showed a stronger antimicrobial against most organisms particularly the Gram-positive bacterial isolates from the respiratory tract, than the other two extracts, while Kola nitida was the least active.